The Impact of Corporate Governance Structures on the Agency Cost of Debt - Chan-Lau, Jorge (IMF Working Papers; Working Paper, 2001)
This paper uses a stochastic continuous time model of the firm to study how different corporate governance structures affect the agency cost of debt. In the absence of asymmetric information, it shows that control of the firm by debtholders with a minority stake delays the exit decision and reduces the underinvestment problem. Such a governance structure may play an important role in diminishing conflicts between shareholders and debtholders.